(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Purpose Sports players reach their peak positions by putting their physical and mental effortsinto practice. Few of them are achieving higher-level certificates and jobs. Most sportspeople havestopped their careers and started a new lifestyle. Method The data from a physical education institutewas used to analyze the performance of male and female sports students’ daily practice sessions. The258 students from various sports, like volleyball, kabaddi, basketball, weightlifting, cricket, football, andathletics, were considered for this analysis. Result The observed frequency data showed fewer malesand females practicing one session daily, and more students were doing two sessions daily. Someaverage numbers of students are practicing three times a day and earning more strength and skills. Theachievements of the three-session practicing students are higher than the data. Chi-square analyseswere performed to detect differences in the number of practice sessions between the sexes. Thesignificant difference for gender and number of practice sessions was 0.05, respectively. ConclusionThis research should help players and coaches understand the importance of three practice sessionsdaily. Therefore, training sessions could be more position-specific, maximising the player’sphysiological outcome in order to optimise performance.